Some Signal Propagation and Traffic Handover Aspects of a Mobile Radio Network for High-Speed Railways - Vlado Lipovac; Antun Sertić; Mateo Milković (Promet (Zagreb), 2012)
Taking advantage of GSM's elaborated mobility managementand its intemational roaming capability, the IntemationalUnion of European Railroad Operators (UJC) has decidedto build a supra-national rail radio network based on enhancedGSM technology.In this pape1; some implemmtation aspects specific to railroadradio environment resulting from the effects of vehiclespeed - in particular Doppler shift - are discussed, and an"off-line" algorithm for the traffic handover is proposed, whichoffers bel/er radio link reliability and less critical timing constraintsthan conventional handover schemes. More reliablehandover is of vital significance in the case of high-speed trainssince the radio link is supposed to cany the automatic controlsignals (ATC), too.